Pengembangan Media Madu pada Materi Perkalian Kelas II Sekolah Dasar - Natali Amelia; Adinda Septia Syafani; Nabilla Syadena; Dihan Meilanriska Syaputri (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to develop learning media based on wall magazine (mading) and dice for teaching multiplication to second-grade students at SD Negeri 212 Palembang. The research employs the Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. After the media was developed, validation was conducted by content experts and media experts to assess its feasibility, as well as trials by practitioners and students to evaluate the practicality and effectiveness of the media. The validation results showed a feasibility score of 87% from content experts and 94% from media experts. Practitioners gave a practicality score of 92%, indicating that the media is very practical for use in teaching. Student trials were carried out in three stages: one-to-one with a practicality score of 98%, small group with 99%, and a field test involving 26 students showed an effectiveness level of 96%. This wall magazine and dice media is effective and practical to be used as learning media for teaching multiplication to second-grade elementary school students.